2015
DOI: 10.1074/jbc.m115.651885
|View full text |Cite
|
Sign up to set email alerts
|

JIP3 Activates Kinesin-1 Motility to Promote Axon Elongation

Abstract: Background: Axon growth and regeneration depend on kinesin-1-dependent transport. Results: JIP3 binding to KHC promotes kinesin-1 motility along microtubules and is essential for axon elongation and regeneration. Conclusion: JIP3 regulation of kinesin-1 motility is critical for axon elongation and regeneration. Significance: Regulation of intracellular transport is important for proper neuronal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 78 publications
0
58
0
1
Order By: Relevance
“…Indeed, there is genetic evidence in mice that JIP3 can function as an adaptor that promotes the Kinesin-1-mediated transport of TrkB receptors as well as one or more unidentified cargos relevant to axon elongation and neuronal degeneration (Huang et al 2011;Sun et al 2013;Sato et al 2015;Watt et al 2015).…”
mentioning
confidence: 99%
“…Indeed, there is genetic evidence in mice that JIP3 can function as an adaptor that promotes the Kinesin-1-mediated transport of TrkB receptors as well as one or more unidentified cargos relevant to axon elongation and neuronal degeneration (Huang et al 2011;Sun et al 2013;Sato et al 2015;Watt et al 2015).…”
mentioning
confidence: 99%
“…This study found that a JIP3 mutant that is unable to bind the motor subunit of kinesin-1 (KHC) (42) leads to slow moving kinesin-1 tetramer. When expressed in cultured hippocampal neurons this JIP3 mutant reduces axon growth despite being properly localized to axon tips (71). This study illustrates that in addition to JIP3-dependent localization at axon tips to mediate axon growth (72), JIP3 controls axon growth via a motor processivity-based mechanism.…”
Section: Figmentioning
confidence: 89%
“…Beyond its role in delivering cargo to and from the axon terminal, axonal transport is emerging as a more sophisticated system to regulate signaling. A recent study revealed that regulation of kinesin-1 motility by JIP3 is critical for axon growth and regeneration (71). This study found that a JIP3 mutant that is unable to bind the motor subunit of kinesin-1 (KHC) (42) leads to slow moving kinesin-1 tetramer.…”
Section: Figmentioning
confidence: 94%
See 1 more Smart Citation
“…Мөн JSAP уургууд нь эсийн дотор карго зөөвөрлөдөг мотор уураг болох кинезин-1 -тэй (kinesin-1) харилцан үйлчилж улмаар каргог мотор уурагтай холбодог болохыг судлаачид тогтоожээ [13][14][15][16]. Сүн нар [17] болон Ватт нар [18] JSAP нь мотор уургийн идэвх ба хөдөлгөөнийг зохицуулдаг болохыг харуулсан [13][14][15][16][17][18]. Мэдрэлийн эсийн аксоны уртсах, салаалах, мэдрэлийн ширхэг үүсэхэд ч JSAP уургууд чухал үүрэгтэй ажээ [19][20][21][22].…”
Section: оршилunclassified